THE ROLE OF ARTIFICIAL INTELLIGENCE IN ENHANCING ENGLISH SPEAKING AND LISTENING SKILLS IN HIGHER EDUCATION - Gilea, Aigerim A.; Katerina V. Melnova; Gyuzelya K. Temirgaliyeva (Proceeding of International Conference on Social Science and Humanity, 2025)
Objective: This study aims to analyze the role and effectiveness of Artificial Intelligence (AI) tools in enhancing English speaking and listening proficiency among EFL learners in higher education. Method: The research adopts a comprehensive literature review approach, synthesizing findings from recent empirical studies and scholarly discussions on AI applications such as Automated Speech Recognition (ASR), chatbots, Intelligent Tutoring Systems (ITS), and immersive technologies. Results: The analysis reveals that AI tools contribute significantly to improving pronunciation accuracy, speaking fluency, and listening comprehension, including intercultural and metacognitive dimensions. Moreover, these tools enhance learner confidence and engagement. Despite these benefits, limitations persist in the development of higher-order interactional competence and the consistent use of active vocabulary. Novelty: This study provides a novel contribution by concurrently examining the impact of AI on both speaking and listening skills, integrating recent advancements such as Generative AI, and offering critical insights for educators and researchers on optimizing AI-assisted language learning environments.